2010
DOI: 10.1186/1471-2296-11-79
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of missed appointments at an urban primary care clinic: a randomised controlled study

Abstract: BackgroundMissed appointments are known to interfere with appropriate care and to misspend medical and administrative resources. The aim of this study was to test the effectiveness of a sequential intervention reminding patients of their upcoming appointment and to identify the profile of patients missing their appointments.MethodsWe conducted a randomised controlled study in an urban primary care clinic at the Geneva University Hospitals serving a majority of vulnerable patients. All patients booked in a prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
0
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 24 publications
5
91
0
7
Order By: Relevance
“…Numerous empirical studies have reported that when a patient fails to keep scheduled clinical appointments, it leads to severe consequences for the patient's health. In addition, missing appointments jeopardizes all types of medical practices, ranging from maternal practice clinics to general practice clinics [1][2][3] . In some medical settings, such as obstetrics, which encompasses pregnancy planning as well as prenatal and postnatal care, missed appointments pose severe health consequences for women both pre-and post-pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous empirical studies have reported that when a patient fails to keep scheduled clinical appointments, it leads to severe consequences for the patient's health. In addition, missing appointments jeopardizes all types of medical practices, ranging from maternal practice clinics to general practice clinics [1][2][3] . In some medical settings, such as obstetrics, which encompasses pregnancy planning as well as prenatal and postnatal care, missed appointments pose severe health consequences for women both pre-and post-pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…While the international rates of missed clinical appointments vary significantly according to the types of maternal healthcare clinics, the evidence indicates that women miss their appointments at rates ranging from 2% to 30%, with higher rates for psychiatric [1] and maternal healthcare [10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are many studies including systematic reviews assessing the use of mobile health technology (mHealth) to address gaps in the cascade of HIV/AIDS care, most of them are focussed on improving health outcomes once the ART has been started but not addressing the gaps between diagnosis and treatment [14,1923]. The interventions that have been tested to improve linkage to or retention in pre-ART care include point-of-care CD4 testing, providing food incentives, home-based ART initiation and health system interventions such as integration of antenatal services with ART care, adoption of WHO guidelines and introduction of a structured pre-ART care [20].…”
Section: Discussionmentioning
confidence: 99%
“…Em clínicas de atenção primária de Genebra, os pacientes faltam a 22% das consultas. 10 No sistema de saúde britânico 6,5% das consultas são perdidas por faltas. 11 Nos EUA a prevalência de faltas varia de 5 a 55%.…”
unclassified